2022
DOI: 10.3126/jbmr.v4i01.46678
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Use of Human Resource Information System in Nepali Organizations

Abstract: Adoption of Human Resource Information System (HRIS) could be instrumental in gaining competitive advantage to organizations across all sectors. However, the adoption of HRIS is scanty in many organizations, especially in the developing countries. This study attempted to investigate application of Unified Technology Acceptance and Use of Technology (UTAUT) model in the context of adoption of Human Resource Information System (HRIS) in Nepali organizations. It also examined the mediating role of Behavioral Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
0
0
Order By: Relevance
“…This further supports the theory of the Technology Acceptance Model by Davis (1989) in which he stated that ease of use and perceived usefulness determine one's behavioral intention to adopt information technology. This ne w discovery is consistent with the corresponding study proposed by past studies (Fobang, Wamba, & Kamdjoug, 2019;Perera & Jayawardana, 2022;Sair & Danish, 2018;Tamrakar & Shrestha, 2022). In addition, the new d iscovery made by the current study will contribute to teachers' belief that strong behavioral intention to use informatization instructional leadership will produce good performance expectancy, and that effort expectancy will help teachers to produce the behavioral intention to adopt informatization instru ctional leadership.…”
Section: The Direct Effect Of Ue Si Fc Cse Btc On Bisupporting
confidence: 90%
“…This further supports the theory of the Technology Acceptance Model by Davis (1989) in which he stated that ease of use and perceived usefulness determine one's behavioral intention to adopt information technology. This ne w discovery is consistent with the corresponding study proposed by past studies (Fobang, Wamba, & Kamdjoug, 2019;Perera & Jayawardana, 2022;Sair & Danish, 2018;Tamrakar & Shrestha, 2022). In addition, the new d iscovery made by the current study will contribute to teachers' belief that strong behavioral intention to use informatization instructional leadership will produce good performance expectancy, and that effort expectancy will help teachers to produce the behavioral intention to adopt informatization instru ctional leadership.…”
Section: The Direct Effect Of Ue Si Fc Cse Btc On Bisupporting
confidence: 90%
“…Hence, researchers have discovered many obstacles impeding HRIS implementation, particularly in underdeveloped nations. (Tamrakar & Shrestha, 2022). Ololade et al (2023) determine that the major impediments to efficient implementation of HRIS include management fear, employee privacy concerns, internal organisational opposition and conversion expenses.…”
Section: Functions Of Human Resource Information Systemmentioning
confidence: 99%
“…Bensaid, (2023) opined that problem becomes apparent as soon as an information system such as the HRIS is being implemented. Researchers have discovered numerous factors affecting HRIS implementation, particularly in developing nations (Tamrakar & Shrestha, 2022). Parkar et al (2021) indicated that an issue that developing nations have when implementing HRIS systems is the high cost of establishing HRIS systems, constructing sufficient IT infrastructure, purchasing computers that meet the requirements of the HRIS, software maintenance, and hardware maintenance.…”
Section: Introductionmentioning
confidence: 99%